PEMBELAJARAN MUSIK PENERAPAN KEGIATAN PROYEK PENGUAT PROFIL PELAJAR PANCASILA KELAS VIII SMP NEGERI 23 BANJARMASIN - Najamudin, Muhammad; Nurul Ilmiah; Maryanto (Program Studi Pendidikan Musik, 2025)
This study aims to describe the process and outcomes of music learning through the implementation of the Pancasila Student Profile Strengthening Project (P5) with the theme of Local Wisdom. The research employs a qualitative method with a descriptive qualitative approach. The research subjects are Grade VIII students at SMP Negeri 23 Banjarmasin. Data collection techniques include observation, interviews, and documentation. Data analysis is conducted through data reduction, data display, and conclusion drawing. The results of the study show that the music learning process using the P5 activities themed Local Wisdom involved five classroom meetings, consisting of three stages: the opening activity, the core activity, and the closing activity. These five meetings reflected student behavior that aligns with the characteristics of the Pancasila Student Profile, which includes elements of faith in God Almighty and noble character, global diversity, critical thinking, independence, collaboration, and creativity. The implementation of P5 activities themed Local Wisdom in music learning was carried out by the teacher with the aim of addressing issues or problems encountered in classroom learning. These activities provided students with knowledge about arts within the context of local culture, particularly that of South Kalimantan. Furthermore, the P5 activities aimed to enhance students’ learning engagement and creativity.